2010
DOI: 10.1021/jp101418f
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of the Thermochemistry for Conversion of Glucose to Levulinic Acid

Abstract: The thermochemistry of the conversion of glucose to levulinic acid through fructofuranosyl intermediates is investigated using the high-level ab initio methods G4 and G4MP2. The calculated gas phase reaction enthalpies indicate that the first two steps involving water molecule elimination are highly endothermic, while the other steps, including additional water elimination and rehydration to form levulinic acid, are exothermic. The calculated gas phase free energies indicate that inclusion of entropic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 39 publications
9
116
2
Order By: Relevance
“…[33][34][35][36] Similar to previous studies, [37][38][39][40] the periodic model of BEA zeolite corresponded to polymorph A. [41] The optimized parameters of the tetragonal BEA unit cell were a = b = 12.657 and c = 26.396 .…”
supporting
confidence: 68%
See 1 more Smart Citation
“…[33][34][35][36] Similar to previous studies, [37][38][39][40] the periodic model of BEA zeolite corresponded to polymorph A. [41] The optimized parameters of the tetragonal BEA unit cell were a = b = 12.657 and c = 26.396 .…”
supporting
confidence: 68%
“…In the case of Brønsted acid catalysis, the unfavorable protonation of the pyranyl O5 site of GP may lead to the formation of fructose. [33,34,42,43] When the reaction is promoted by Lewis acids, the direct coordination of the O sites of GP to the active site is the key to the selective FF formation. [13,20,23,44,45] Previously, the isomerization by a heterogeneous Sn-BEA catalyst has been postulated to proceed through the O5-coordination of GP to the lattice Sn site (Figure 2 a) followed by a concerted O1H deprotonation and ring-opening reactions.…”
Section: Resultsmentioning
confidence: 99%
“…45,46 Th e effi cient and optimised production of levulinic Th e thermochemistry of conversion of glucose to levulinic acid through fructofuranosyl intermediates was investigated by Assary and co-workers. 64 Th ey found that the fi rst two dehydration steps are highly endothermic likely indicating these to be key steps in controlling the overall progress of the reaction, while the other steps, including the additional water elimination and rehydration to form levulinic acid, are exothermic. Th e dehydration reaction steps were predicted to be more favourable thermodynamically under elevated temperatures and aqueous reaction environments.…”
Section: Lignocellulosic Feedstocksmentioning
confidence: 99%
“…In contrast, reactions of water-soluble sugars with solid acid catalysts have been extensively studied [8,14,65,78,87,88,115]. In general, the heterogeneous catalytic system could convert water-soluble sugars to organic acids by shape-selective, solid acid-catalyzed processes at low temperatures.…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%